2019
DOI: 10.3390/jcm8060783
|View full text |Cite
|
Sign up to set email alerts
|

MaioRegen Osteochondral Substitute for the Treatment of Knee Defects: A Systematic Review of the Literature

Abstract: Background: This study aims to investigate the clinical and radiological efficacy of three-dimensional acellular scaffolds (MaioRegen) in restoring osteochondral knee defects. Methods: MEDLINE, Scopus, CINAHL, Embase, and Cochrane Databases were searched for articles in which patients were treated with MaioRegen for osteochondral knee defects. Results: A total of 471 patients were included in the study (mean age 34.07 ± 5.28 years). The treatment involved 500 lesions divided as follows: 202 (40.4%) medial femo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 44 publications
(161 reference statements)
1
34
0
3
Order By: Relevance
“…The bone-layer of TruFit CB is made of PGA and calcium phosphate, two materials that degrade quickly post-implantation and mechanical failure has resulted in the plug being withdrawn from the market (Fraser et al, 2016 ; Tseng et al, 2020 ). D'Ambrosi et al ( 2019 ), investigated the clinical and radiological efficacy of MaioRegen, a try-layered collagen-based scaffold, in restoring osteochondral knee defects. Despite the promising satisfactory and reliable results at mid-term follow-up, this systematic review revealed that, in terms of clinical improvement at follow-up, MaioRegen is not superior to conservative treatment or other cartilage techniques.…”
Section: Current Clinical Therapiesmentioning
confidence: 99%
“…The bone-layer of TruFit CB is made of PGA and calcium phosphate, two materials that degrade quickly post-implantation and mechanical failure has resulted in the plug being withdrawn from the market (Fraser et al, 2016 ; Tseng et al, 2020 ). D'Ambrosi et al ( 2019 ), investigated the clinical and radiological efficacy of MaioRegen, a try-layered collagen-based scaffold, in restoring osteochondral knee defects. Despite the promising satisfactory and reliable results at mid-term follow-up, this systematic review revealed that, in terms of clinical improvement at follow-up, MaioRegen is not superior to conservative treatment or other cartilage techniques.…”
Section: Current Clinical Therapiesmentioning
confidence: 99%
“…Recently, D’Ambrosi et al (2019) published a systematic review on the results of MaioRegen. MaioRegen being a triphasic scaffold aims to closely resemble the osteochondral unit.…”
Section: Clinical Results Of Osteochondral Implantsmentioning
confidence: 99%
“…The scaffolds have different layers that promote the concurrent restoration of subchondral bone and cartilage. 26,27 Despite extensive preclinical research in the field of biomaterials, only a few osteochondral scaffolds have reached clinical practice, 8,32,45 and in spite of promising results demonstrated in animal models, their regenerative potential in the human setting has thus far shown less favorable outcomes, especially concerning the subchondral bone. The first scaffold available was a bilayered cylindrical implant made of a PLGA copolymer, for which controversial results were demonstrated.…”
Section: Discussionmentioning
confidence: 99%